IDENTIFICATION OF ESCHERICHIA COLI AND SALMONELLA SP. ON FRIED SNACKS SOLD ON THE UNIMA CAMPUS ENVIRONMENT - Runtunuwu, Yudistira Deyvan; Lawalata, Helen J; Tengker, Anita (Indonesian Biodiversity Journal, 2024)
This study aims to explain how bacterial contamination and the presence of Escherichia coli and Salmonella sp. on fried bananas sold in the UNIMA campus environment. This exploration used clear qualitative subjective observation with the TPC strategy for all total bacterial contamination and involved specific media for Escherichia coli and Salmonella sp. From the results of the review, it was found that 1 out of 3 experimental examples of complete bacterial contamination exceeded the threshold set by the Food and Drug Supervisory Agency of the Republic of Indonesia (BPOM RI) in 2016, with the most extreme obstacle being the number of microorganisms in food being 10-4 colonies/ g. Of the 3 samples tried, all samples were identified with Escherichia coli and Salmonella sp. Based on the research conducted, it can be concluded that, of all the observed fried samples, all detected bacterial colonies